The Faltering State : Pakistan's Internal Security Landscape - Tariq Khosa (Karachi Oxford University Press, 2017)
This book reviews the recent internal security challenges facing Pakistan. It is a timely and valuable addition to the literature on the subject of governance and the rule of law.
Include Index and Acknowledgment
Keywords: Terrorism--Prevention -- Politics and government -- Insurgency